Akibat Hukum Batalnya Akta Sewa Menyewa Menurut Gugatan Actio Pauliana dalam Kepailitan - Fazahra Arlia Putri; Jum Anggriani; Fitra Deni (Jurnal Hukum Lex Generalis, 2025)
The importance of the curator's role in the process of managing and settling bankrupt assets cannot be separated from the legal actions carried out by the bankrupt debtor to transfer assets included in the bankrupt estate to another party before being declared bankrupt by the court. The problem in this study is regarding the position of the lessee due to the cancellation of the lease deed based on the action Pauliana lawsuit in Decision Number 43 / Pdt.Sus-Other Lawsuits / 2023 / PN.Niaga.Smg and the responsibility of the Notary due to the lease deed being null and void by law based on the action Pauliana lawsuit in Decision Number 43 / Pdt.Sus-Other Lawsuits / 2023 / PN.Niaga.Smg. This thesis, using normative legal research method (library) with qualitative analysis of secondary data to obtain conclusions about the position of the lessee due to the cancellation of the lease deed based on the action Pauliana lawsuit in Decision Number 43 / Pdt.Sus-Other Claims / 2023 / PN.Niaga.Smg, namely not as any creditor (separatist, preference, concurrent) in the bankruptcy of PT. Lanisantoso Setiabudi, Andri Santoso & Lani Haryati. This is because the Panel of Judges decided and stated that Defendant I, Defendant II and Defendant III must return the money amounting to Rp. 2,500,000,000, - (two billion five hundred million rupiah) to Defendant IV in full and immediately. The Notary's liability due to the lease deed being null and void based on the Pauliana action lawsuit in Decision Number 43/Pdt.Sus-Other Claims/2023/PN.Niaga.Smg, can be requested according to the code of ethics with sanctions in the form of written warnings, temporary suspension, honorable dismissal and dishonorable dismissal. Civil, by filing a lawsuit for compensation to the District Court experienced by the tenant due to the lease deed made before the Notary being null and void.